2017
DOI: 10.1080/01639625.2017.1304803
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Interaction in Webcam Sex Work: A Comparative Analysis of Female and Male Broadcasters

Abstract: categorizada como INVESTIGACIÓN SIN RIESGO, debido a que no se desarrolla ninguna intervención o proceso invasivo.Beneficios de la participación: La actividad no garantiza, ni promete que el participante recibirá beneficio económico.Voluntariedad: Su participación es totalmente voluntaria y puede retirarse si así lo desea, sin ninguna sanción o consecuencia.Confidencialidad: Los datos suministrados por usted durante el ejercicio de la aplicación y el análisis de las pruebas no serán divulgados a terceros y se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The digital technology user can be in the role of both the commercial service provider (e.g., providing a live sex show via webcam for paying subscribers; Bleakley, 2014 ) or the client (e.g., paying to watch a live sex show via webcam; Weiss, 2018 ). While some authors describe low-threshold commercial webcam sex as a problem because it expands the commercial sex market and fosters a general commodification of sex, other authors point to the advantages of mediated commercial sex free from any risk of STI transmission or physical violence.…”
Section: Conceptual Analysis Of Sexual Interaction In Digital Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital technology user can be in the role of both the commercial service provider (e.g., providing a live sex show via webcam for paying subscribers; Bleakley, 2014 ) or the client (e.g., paying to watch a live sex show via webcam; Weiss, 2018 ). While some authors describe low-threshold commercial webcam sex as a problem because it expands the commercial sex market and fosters a general commodification of sex, other authors point to the advantages of mediated commercial sex free from any risk of STI transmission or physical violence.…”
Section: Conceptual Analysis Of Sexual Interaction In Digital Contextsmentioning
confidence: 99%
“…At the same time, technology-mediated sexual interactions are described as risky, particularly because of boundary violations and non-consensual behaviors such as dissemination or publication of privately shared intimate messages against the will of the participant (e.g., so-called “revenge porn” or “image-based abuse”), non-consensual moves during the interaction (e.g., unsolicited sending of sexually explicit images such as “dick pics”) and technology-mediated sexual abuse of children (e.g., adults manipulating children into sending semi-nude pictures; Henry et al, 2018 ; Mandau, 2020 ; Mckinlay and Lavis, 2020 ; Naezer and van Oosterhout, 2021 ). In the context of commercial sex, the literature generally portrays technology-mediated sex work as a safer form of sexual labor that allows services providers even to become entrepreneurs ( Podlas, 2000 ; Bleakley, 2014 ; Selmi, 2014 ; Jones, 2016 ; Weiss, 2018 ). At the same time, digital commercial sex services in the form of technology-mediated live interactions are associated with specific risks such as harassment or child prostitution ( Jones, 2016 ; Açar, 2017 ; see Table 5 ).…”
Section: Sexual Interaction Via Digital Technologiesmentioning
confidence: 99%
“…A qualitative analysis of activities of male and female performers on http://flirtcams.com revealed that interactions were not notably distinguishable by gender, but differed between professionals (defined by the amount of time broadcasting) and occasional performers (Weiss, ). Three patterns of interaction turned out to be characteristic of professional performers: sharing personal information with viewers, deferring to their specific wishes and suggestions, and conducting dynamic shows.…”
Section: Resultsmentioning
confidence: 99%
“…International Journal of Gender, Sexuality and Law 174 I utilise these terms also. Within the academic literature, there is a tendency to research performers who broadcast from tipping sites such as Chaturbate (Bleakley, 2014;Jones, 2015b;Weiss, 2017;Jones, 2020;Van Doorn & Velthuis, 2018); this work seeks to address that imbalance. Although I interviewed women who worked from both tipping and private sites, the narratives that I use in this article are about women's experiences working on private sites mainly but not exclusively Streamate because the majority of women I spoke with broadcast from Streamate.…”
Section: Peer-reviewed Articlementioning
confidence: 99%